Thermal gradient pattern of shallow pitting via active thermography-water and steam - Ismon, Maznan; Chai, Ronnie; Ismail, Al Emran; Zainulabidin, Muhd Hafeez; Mat Noor, Fazimah; Abd Wahab, Hanani; Mohamad, Zaleha; Madlan, Mohd Amran; Zaman, Izzuddin (Penerbit UTHM, 2018)
Pipelines are extensively used worldwide to transport water, oil and gas. Wall thinning or pits can be produced in the internal of the pipe after being used for a certain period of the time due to some factor such as erosion-corrosion and pitting corrosion. This problem concern lots of company in various industry because leakage of pipe cause system failure, hazard at workplace and increase of maintenance cost. This study detected internal wide and shallow pitting of pipe using infrared thermography. ASTM A106 Grade B carbon steel pipe test specimen was drill with five similar size defects shallow pitting within different depth. The result found that all defects appear at 90°C temperature exposure, while only four defects appear at 70°C and 80°C of temperature exposure. This is due to the higher temperature introduced into the pipe, the higher temperature gradient could be observed. Introducing a 90°C of heat source will produce the shortest time for the spot to appear while for 70°C take the longest time. Image analysis software assists to conclude that the defect areas are within 146% to 222% larger than the actual size at pipe.